2019
DOI: 10.3389/fpsyg.2019.01224
|View full text |Cite
|
Sign up to set email alerts
|

Young-Old City-Dwellers Outperform Village Counterparts in Attention and Verbal Control Tasks

Abstract: Cognitive performance is dynamic and shaped by individual biological and environmental factors throughout life. In psychology, besides the effects of age, education, and other often studied factors, the complexity of the lived-in environment and urbanicity in that context are yet to be elucidated. In this observational cross-sectional study, we compare cognitive performance in standard neuropsychological tests in healthy older persons from three different types of settlements in the Czechia: the capital city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
1
2
0
Order By: Relevance
“…The cognitive performance findings mirror those in the aging literature, which posits that rural dwellers may suffer greater cognitive impairment than urban residents [62,63]. Factors of urban life, such as complex living environments, time-pressured problem solving, leisure-time activities, and increased likelihood of personal interactions, have been identified as stimulating factors for attention, verbal memory, and visual processing [62]. As such, interventions targeting modifiable risk factors for cognitive decline (e.g., PA) may be specifically important in rural BCS.…”
Section: Discussionsupporting
confidence: 73%
“…The cognitive performance findings mirror those in the aging literature, which posits that rural dwellers may suffer greater cognitive impairment than urban residents [62,63]. Factors of urban life, such as complex living environments, time-pressured problem solving, leisure-time activities, and increased likelihood of personal interactions, have been identified as stimulating factors for attention, verbal memory, and visual processing [62]. As such, interventions targeting modifiable risk factors for cognitive decline (e.g., PA) may be specifically important in rural BCS.…”
Section: Discussionsupporting
confidence: 73%
“…A study from the Czech Republic suggested that living in a big city is associated with higher cognitive performance only in some domains [ 42 ]. They found better memory, attention and verbal control performance in the citizens of Prague in comparison to other areas (towns, villages).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is some evidence suggesting a positive association between green space around the home address and well-being in children and a negative association with depressive symptoms in adolescents and young adults (Vanaken & Danckaerts, 2018). The most prominent exception to the benefits of green space on mental health seems to be observed in older adults, where dementia is reported to be less frequent in urban compared to rural areas and cognitive performance seems to be higher in more urban areas (Georgi et al, 2019; Robbins et al, 2019). To better understand the potential underlying brain-based mechanisms of these mental health effects of green space exposure, neuroimaging studies are needed, that associate green space with brain structure.…”
mentioning
confidence: 99%